N-Doping of organic semiconductors for enhanced electron extraction from solution processed solar cells using alkali metals. Issue 38 (13th September 2016) - Schneider, Tanja; Czolk, Jens; Landerer, Dominik; Gärtner, Stefan; Puetz, Andreas; Bruns, Michael; Behrends, Jan; Colsmann, Alexander
Abstract : Organic solar cells: sodium-doped electron extraction layers processed from toluene solution. Abstract : To improve charge carrier injection into or extraction from organic optoelectronic devices, electrically doped layers are often employed. Whereas n-doping of organic semiconductors has been widely used in vacuum processed optoelectronic devices, adequate solution processes to enable future device printing are underdeveloped. In this work, we study n-doping of 1, 3, 5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) in a solution process, using sodium as the electron donor. Upon addition of elementary sodium to a clear TPBi/toluene solution, we observed a change in color, indicating charge carrier transfer between sodium and TPBi. The optical and electrical properties of doped and undoped TPBi were characterized in solution and in the corresponding thin-films. Electron Paramagnetic Resonance (EPR) measurements revealed an increase of the number of unpaired spins upon doping, indicating the presence of doping-induced charge carriers. Implementing TPBi : Na as electron extraction layers in organic solar cells, we found almost the same device performance as compared to state-of-the-art solar cells comprising zinc oxide electron extraction layers.